Jews in Ukrainian literature : representation and identity - Shkandrij, Myroslav, 1950- (Yale University Press, 2009)
This pioneering study is the first to show how Jews have been seen through modern Ukrainian literature. Myroslav Shkandrij uses evidence found within that literature to challenge the established view that the Ukrainian and Jewish communities were antagonistic toward one another and interacted only when compelled to do so by economic necessity. Jews in Ukrainian Literature synthesizes recent research in the West and in the Ukraine, where access to Soviet-era literature has become possible only in the recent, post-independence period. Many of the works discussed are either little-known or unknown in the West. By demonstrating how Ukrainians have imagined their historical encounters with Jews in different ways over the decades, this account also shows how the Jewish presence has contributed to the acceptance of cultural diversity within contemporary Ukraine.